Hubungan Perilaku Seksual Pada Odha Dengan Tingkat Kecemasan Terkait IMS - Ryian Aryiani; Nur Azizah Indriastuti (Malahayati Nursing Journal, 2025)
ABSTRACT Sexual behavior that involves changing partners causes an increase in STIs. Higher risk of transmission comes from sexual behavior in People with HIV/AIDS (PLWHA). Sexual behavior in PLWHA can have a negative impact on psychological health, such as anxiety. This is because PLWHA are worried about contracting STIs or transmitting them to their partners. This study aims to determine the relationship between sexual behavior and anxiety levels. This study used a non-experimental quantitative approach with a cross-sectional design. The sample consisted of 60 PLWHA at the Victory Plus Foundation in Yogyakarta, selected through purposive sampling techniques. Data were collected using a questionnaire on sexual behavior and anxiety levels. The results showed that the majority were 30 years old, 31 respondents (50.8%). Male gender 45 respondents (73.8%). The last level of education was high school/equivalent 38 respondents (62.3%). Unemployed 24 respondents (39.3%). Social support 33 respondents (54.1%). The anxiety level in PLWHA was mostly mild, as many as 32 respondents (51.6%). Sexual behavior in PLWHA was mostly risky, as many as 50 respondents (80.6%). Based on the chi-square test, there was a significant relationship between the sexual behavior questionnaire and anxiety levels. Keywords: Sexual Behavior, Anxiety Level ABSTRAK Perilaku seksual yang berganti-ganti pasangan menyebabkan peningkatan penyakit IMS. Penularan yang lebih berisiko berasal dari perilaku seksual pada Orang Dengan HIV /AIDS (ODHA). Perilaku seksual pada ODHA dapat memberikan dampak buruk pada kesehatan psikologis, seperti kecemasan. Hal ini dikarenakan ODHA merasa khawatir tertular IMS atau menularkan kepada pasangan.  Penelitian ini bertujuan untuk mengetahui hubungan perilaku seksual dengan tingkat kecemasan. Penelitian ini menggunakan pendekatan kuantitatif non ekprimental dengan desain cross sectional. Sampel terdiri dari 60 ODHA di Yayasan Victory Plus Yogyakarta, dipilih melalui teknik purposive sampling.Data dikumpulkan menggunakan kuesioner perilaku seksual dan tingkat kecemasan. Hasil penelitian menunjukkan bahwa mayoritas berusia 30 tahun sebanyak 31 responden (50,8 %). Jenis kelamin laki-laki 45 responden (73,8 %). Jenjang pendidikan terakhir SMA/sederajat 38 responden (62,3 %). Tidak bekerja 24 responden (39,3 %). Dukungan sosial 33 responden (54,1 %). Tingkat kecemasan pada ODHA mayoritas ringan sebanyak 32 responden (51,6%). Perilaku seksual pada ODHA mayoritas berisiko sebanyak 50 responden (80,6%).  Berdasarkan Uji chi-square menunjukkan adanya hubungan yang signifikan antara kuesioner perilaku seksual dan tingkat kecemasan. Kata Kunci: Perilaku Seksual, Tingkat Kecemasan